2018
DOI: 10.1038/s12276-018-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 axis mediates hyperplasia of intrarenal urothelium in obstructive renal injury

Abstract: The monolayered intrarenal urothelium covers the renal papilla and ureteropelvic junction (UPJ). In response to increased renal pressure during obstruction or ischemic injuries, intrarenal urothelial cells begin to proliferate and form a multilayered urothelium. Little is known regarding the mechanism and pathophysiological role of urothelium hyperplasia during renal obstruction. In this study, we investigated the expression of interleukin (IL)-33, an IL-1 family cytokine, in kidneys with unilateral ureteral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Li et al reported that exogenous IL-33 promotes kidney fibrosis via the effector function of AAMs in the UUO model [55]. Our previous study investigated the ST2+ immune cell profile in the kidney, which revealed that the myeloid cells are the major targets of IL-33 in the UUO-induced obstructed kidney [58]. However, the deletion of Il33 reduced the protein levels of type 2 cytokines in the urine isolated from the UUO kidney [58].…”
Section: Roles Of Endogenous Il-33 Versus Exogenous Il-33 In Kidney Imentioning
confidence: 88%
See 4 more Smart Citations
“…Li et al reported that exogenous IL-33 promotes kidney fibrosis via the effector function of AAMs in the UUO model [55]. Our previous study investigated the ST2+ immune cell profile in the kidney, which revealed that the myeloid cells are the major targets of IL-33 in the UUO-induced obstructed kidney [58]. However, the deletion of Il33 reduced the protein levels of type 2 cytokines in the urine isolated from the UUO kidney [58].…”
Section: Roles Of Endogenous Il-33 Versus Exogenous Il-33 In Kidney Imentioning
confidence: 88%
“…In addition to kidney ILC2s, other ST2-expressing immune populations were also identified. Among the ST2+ cells, the CD45-non-leukocytes, neutrophils, macrophages, T/ILCs, and monocytes comprised 34.8%, 22.3%, 23.1%, 16.2%, and 3.6%, respectively [58]. Compared with the nonobstructed kidneys, the UUO kidneys exhibited a 30-fold increase in the number and a 4.6-fold increase in the percentage of ST2+ neutrophils [58].…”
Section: Characterization Of Il-33-responsive Kidney Ilc2smentioning
confidence: 99%
See 3 more Smart Citations